2008
DOI: 10.1186/1749-8546-3-2
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on using acupuncture and transcutaneous electrical nerve stimulation (TENS) to treat knee osteoarthritis (OA)

Abstract: BackgroundThe present study tests whether a combined treatment of acupuncture and transcutaneous electrical nerve stimulation (TENS) is more effective than acupuncture or TENS alone for treating knee osteoarthritis (OA).MethodsThirty-two patients with knee OA were randomly allocated to four groups. The acupuncture group (ACP) received only acupuncture treatment at selected acupoints for knee pain; the TENS group (TENS) received only TENS treatment at pain areas; the acupuncture and TENS group (A&T) received bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
0
36
0
3
Order By: Relevance
“…19 In cases in which pharmacological treatment is ineffective and the criteria for surgery are not fulfilled, or when surgery is refused by the patient, alternative methods for pain relief such as Acupuncture and Homeopathy can be considered. 5 In this study, pain has improved statistically on both VAS of pain and pain subscale of the WOMAC in group I (acupuncture treated group). The number of tender points decreased significantly, and moreover, there was significant decrease in the number of patients receiving analgesics for pain control (p<0.05).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…19 In cases in which pharmacological treatment is ineffective and the criteria for surgery are not fulfilled, or when surgery is refused by the patient, alternative methods for pain relief such as Acupuncture and Homeopathy can be considered. 5 In this study, pain has improved statistically on both VAS of pain and pain subscale of the WOMAC in group I (acupuncture treated group). The number of tender points decreased significantly, and moreover, there was significant decrease in the number of patients receiving analgesics for pain control (p<0.05).…”
Section: Discussionmentioning
confidence: 94%
“…4 The pharmacologic therapies used in treatment of OA may often cause unwanted and dangerous side effects. 5 Many studies have documented that acupuncture has a beneficial effect when treating many diseases and painful conditions, and therefore is thought to be useful as a complementary therapy or to replace generally accepted pharmacological intervention. 6 It is proposed that acupuncture produces its effects by the conduction of electromagnetic signals at a greaterthan-normal rate, thus aiding the activity of painkilling biochemicals , such as endorphins and immune system cells at specific sites in the body.…”
Section: Introductionmentioning
confidence: 99%
“…56 Regarding other potential sources of bias (including lack of intention-to-treat analysis, information about cointerventions, compliance, acceptability and baseline comparisons), 16 studies were found to demonstrate an unclear risk of bias due to the lack of intention-to-treat analysis, insufficient information about cointerventions, compliance and acceptability. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Additionally, one of these trials failed to report baseline WOMAC and VAS information. 56 The completeness of the STRICTA checklist for each study is detailed in table 2.…”
Section: Study Qualitymentioning
confidence: 99%
“…These 19 studies were published between 1992 and 2014. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] The number of participants in the studies varied from 20 to 712. Two studies were conducted in the USA, [43][44][45] three in Germany, 46 58 59 four in China, 47-49 61 three in the UK, 52 56 57 and one each in Australia, 50 Japan, 51 Greece, 53 Iran, 54 Thailand 55 and Denmark.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation